2021
DOI: 10.1186/s12876-021-01939-7
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing findings of liver fibrosis following COVID-19

Abstract: Background Studies on a new coronavirus disease (COVID-19) show the elevation of liver enzymes and liver fibrosis index (FIB-4) independently on pre-existing liver diseases. It points to increased liver fibrogenesis during acute COVID-19 with possible long-term consequences. This study aimed to assess liver fibrosis in COVID-19 patients by serum hyaluronic acid (HA) and FIB-4. Methods The study included the acute COVID-19 group (66 patients, 50% f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 33 publications
(55 reference statements)
0
12
0
4
Order By: Relevance
“…Pulmonary fibrosis and liver fibrosis are among critical complications in severe COVID-19 patients [34] , [35] , [36] . Therefore, it is imperative to understand the underlying pathomechanisms of tissue fibrosis observed in COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary fibrosis and liver fibrosis are among critical complications in severe COVID-19 patients [34] , [35] , [36] . Therefore, it is imperative to understand the underlying pathomechanisms of tissue fibrosis observed in COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…PI3K–Akt signaling is also involved in the development of fibrotic processes [ 98 , 99 ] in the lungs [ 100 , 101 ] and liver; of note, COVID-19-related liver fibrosis can develop independently of pre-existing chronic liver disease [ 102 ]. The link between liver fibrogenesis, microRNA, and the PI3K signaling pathway was investigated; in an experimental liver fibrosis model, Lei et al reported that miR-101 has a strong antifibrotic effect through downregulation of the PI3K-Akt signaling pathway [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, the liver injury in COVID-19 patients is acute but transient and mild, and commonly with minimal inflammation, albeit the fatal liver damages have also been sparsely reported in the previously heathy COVID-19 patients (42,43). Insofar, health outcomes following 6, 12, and 24 months after disease onset have not specified the expansive liver-related consequence in long COVID cases (44); however, increased liver fibrogenesis was notified in patients 3-6 months post COVID (45).…”
Section: Discussionmentioning
confidence: 99%